2022
DOI: 10.1177/00238309211071045
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linguistic Trends in Speech Errors: An Analysis of Sub-Lexical Errors in Cantonese

Abstract: Though past research on the sound structure of speech errors has contributed greatly to our understanding of phonological encoding, most of this research comes from a small set of majority languages with similar linguistic structures. To increase the linguistic diversity of relevant evidence, a large collection of speech errors was investigated in Cantonese, an under-studied language with unique phonological structures. In particular, the Cantonese data were examined for nine psycholinguistic effects commonly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…As has been noted in anthologised volumes on word form encoding in particular (Meyer & Belke, 2007), and language production in general (Costa et al., 2007; Griffin & Crew, 2012), most of the generalisations supporting the consensus model have come from investigations of Indo‐European languages, and as such they do not fully reflect the diversity of human language. Indeed, literature surveys of language production research (Alderete, 2022; Chen et al., 2002) have shown that this research has a strong bias towards the Indo‐European languages and other major languages of the world, reflecting the same bias found in the larger field of psycholinguistics (Anand et al., 2011).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…As has been noted in anthologised volumes on word form encoding in particular (Meyer & Belke, 2007), and language production in general (Costa et al., 2007; Griffin & Crew, 2012), most of the generalisations supporting the consensus model have come from investigations of Indo‐European languages, and as such they do not fully reflect the diversity of human language. Indeed, literature surveys of language production research (Alderete, 2022; Chen et al., 2002) have shown that this research has a strong bias towards the Indo‐European languages and other major languages of the world, reflecting the same bias found in the larger field of psycholinguistics (Anand et al., 2011).…”
Section: Introductionmentioning
confidence: 84%
“…The word onset effect in speech errors is cross‐linguistically robust. Above chance rates of errors in word initial position have been found in German (Berg, 1991), two large studies of English (Shattuck‐Hufnagel, 1987; Vousden et al., 2000), Cantonese (Alderete, 2022), and Korean (Han et al., 2019). However, Spanish sound errors appear to contravene this consensus.…”
Section: Serial Order and Starting Pointsmentioning
confidence: 95%
See 2 more Smart Citations
“…In Dutch, for example, there are indeed many phoneme errors when compared with syllabic errors. However, Alderete (2022) has shown that phoneme slips are also relatively frequent in Chinese (e.g., additions such as /uk55/ → luk55 “house”), yet, significant numbers of syllable errors also exist in Cantonese 1 . However, the existence of phoneme slips in Cantonese does not mean that the Cantonese IPU is the phoneme (as far as we know no significant onset effects are found in Cantonese experiments investigating the IPU).…”
Section: Methodsmentioning
confidence: 99%